Structural Modeling Using 2D Shell Element to Predict the Initial Plastic Condition of Tubular Frame Structures. Issue 1 (June 2020) - Asykur,; Hadiwidodo, Y S; Handayanu,
Abstract: A Fixed Jacket Platform is usually designed using tubular structures in which every steel pipe has a thickness and diameter. Generally, for the structural analysis of this structure, the tubular members are represented using 1D beam elements. But stress distribution, plastic strain and also ovalization around the tubular member cannot be determined by a beam element. In this research, all tubular structures were modeled using 2D shell elements to identify how the stress distribution around a tubular member is. And the non-linear analysis was carried out to identify the initial plastic condition. This study was focusing on the splash zone where this area was assumed to be exposed to the extreme wave in 8 directions according to the API RP2A-WSD code, in addition to the structure weight and deck load. Due to each direction of the wave loads, the stress distribution and initial plastic condition are studied. The modeling and non-linear static analysis in this study were done using Altair Hyperworks software.